Glossophobia in Training of Speech - Fathu Rahman; ' Nahliah (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
Glossophobia which is known as social phobia is a big problem in delivering a speech.  As such, this research is purposed to thoroughly investigate the problems faced by the students in training of speech in Darul-Huffadh Islamic boarding school of Tujutuju, Kajuara, Bone. With regard to the methodology applied in this study, a qualitative approach was used to describe the data that was discovered from the field through observation with the questionnaire and in-depth interview and field note. In addition, forty-one students were chosen as samples, whilst only ten were selected and invited to have an in-depth interview; these were chosen by using purposive sampling. Finally, the major implication of this study is to confront the problems dealt with the students in training of speech as a recommendation in education that should be taken into account and needs to be solved immediately and for the other researcher to conduct in-depth investigations of research to produce a better outcomes.Keywords: Glossophobias, Speaking Performance, Training of Speech